Glymphatic system: an emerging therapeutic approach for neurological disorders - Gao, Ying; Liu, Kangding; Zhu, Jie (Frontiers in Molecular Neuroscience, 2023)
The functions of the glymphatic system include clearance of the metabolic waste and modulation of the water transport in the brain, and it forms a brain-wide fluid network along with cerebrospinal fluid (CSF) and interstitial fluid (ISF). The glymphatic pathway consists of periarterial influx of CSF, astrocyte-mediated interchange between ISF and CSF supported by aquaporin-4 (AQP4) on the endfeet of astrocyte around the periarterioles, and perivenous efflux of CSF. Finally, CSF is absorbed by the arachnoid granules or flows into the cervical lymphatic vessels. There is growing evidence from animal experiments that the glymphatic system dysfunction is involved in many neurological disorders, such as Alzheimer’s disease, stroke, epilepsy, traumatic brain injury and meningitis. In this review, we summarize the latest progress on the glymphatic system and its driving factors, as well as changes in the glymphatic pathway in different neurological diseases. We significantly highlight the likely therapeutic approaches for glymphatic pathway in neurological diseases, and the importance of AQP4 and normal sleep architecture in this process.